2023
DOI: 10.3390/molecules28062765
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Asymmetric Dearomative [3+2] Cycloaddition of Nitroheteroarenes with Azomethines

Abstract: Catalytic asymmetric dearomative [3+2] cycloaddition of α-imino γ-lactones with either 3-nitroindoles or 2-nitrobenzofurans by using a chiral copper complex as the catalyst was developed. A wide range of structurally diverse polyheterocyclic compounds containing spirocyclic-fused butyrolactone-pyrrolidine-indoline and butyrolactone–pyrrolidine–dihydrobenzofuran skeletons could be smoothly obtained with excellent results (>99:1 dr and 98% ee). The potential synthetic applications of this methodology were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Therefore, we speculated that conducting the dearomative (3 + 2) cycloaddition reaction between para -quinamines and 2-nitrobenzofurans would lead to the fusion of hydroindoline-5-one and 2,3-dihydrobenzofuran. As part of our ongoing research on the dearomatization of electron-deficient heteroarenes [ 54 , 55 , 56 , 57 ], herein, we will report the first nitrogen nucleophile-triggered dearomative (3 + 2) cycloaddition reaction of 2-nitrobenzofurans by using para -quinamines to construct benzofuro[3,2- b ]indol-3-one skeletons ( Scheme 1 c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we speculated that conducting the dearomative (3 + 2) cycloaddition reaction between para -quinamines and 2-nitrobenzofurans would lead to the fusion of hydroindoline-5-one and 2,3-dihydrobenzofuran. As part of our ongoing research on the dearomatization of electron-deficient heteroarenes [ 54 , 55 , 56 , 57 ], herein, we will report the first nitrogen nucleophile-triggered dearomative (3 + 2) cycloaddition reaction of 2-nitrobenzofurans by using para -quinamines to construct benzofuro[3,2- b ]indol-3-one skeletons ( Scheme 1 c).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that conducting the dearomative (3 + 2) cycloaddition reaction between para-quinamines and 2-nitrobenzofurans would lead to the fusion of hydroindoline-5-one and 2,3-dihydrobenzofuran. As part of our ongoing research on the dearomatization of electron-deficient heteroarenes [54][55][56][57], herein, we will report the first nitrogen nucleophile-triggered dearomative (3 + 2) cycloaddition reaction of 2-nitrobenzofurans by using para-quinamines to construct benzofuro [3,2-b]indol-3-one skeletons (Scheme 1c). In recent years, extensive research on the dearomative cyclization reaction benzofuran has revealed the significant potential of this strategy in the con polycyclic compounds containing a 2,3-dihydrobenzofuran core (Scheme 1, t Among the numerous transformations with respect to the dearomative cycliz tion of 2-nitrobenzofurans, the carbon nucleophile-triggered dearomative (3 and (5 + 2) cyclization reactions have been extensively studied [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%